Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Berbantuan Video Pembelajaran terhadap Pemahaman Siswa Kelas 7 SMP - Argulana Candra Hariyanto; Isbadar Nursit; Fadhila Kartika Sari; Dyah Werdiningsih (FKIP Universitas Mataram, 2026)
This study aims to examine the effect of the Contextual Teaching and Learning (CTL) model on students’ mathematics achievement. The study is motivated by the need for instructional approaches that connect mathematical concepts to real-life contexts in order to enhance students’ understanding and engagement. A quantitative approach was employed using a quasi-experimental design with a pretest–posttest control group. The participants consisted of two classes: an experimental group taught using CTL and a control group taught using conventional instruction, with 30 students in each group. The research instrument was a mathematics achievement test scored on a 0–100 scale, administered as both a pretest and a posttest. Data were analyzed using prerequisite tests (normality and homogeneity) followed by an independent-samples t-test at a 0.05 significance level. The results indicate a statistically significant difference in posttest mathematics achievement between students who learned through CTL and those who received conventional instruction. These findings suggest that CTL is more effective in supporting students’ conceptual understanding and their ability to apply mathematical ideas through meaningful, context-based learning activities. Therefore, CTL is recommended as an alternative instructional model to improve students’ mathematics learning outcomes.